Numerical results concerning a sharp adaptive density estimator - Cristina Butucea (Humboldt University of Berlin, Interdisciplinary Research Project 373: Quantification and Simulation of Economic Processes, 1999)
We give here a simulation study of a density estimator, issued from sharp adaptive estimation. This nonparametric estimator was previously proved to have interesting theoretical properties. In this paper we describe the method and apply it successfully to i.i.d. simulated data issued from different densities.
urn:nbn:de:kobv:11-10046225
Keywords: 330; pointwise density estimation; adaptivity; kernel estimator; Lepski's criterion; simulation study